Features of Microelement Homeostasis in Children Living in the Modern City and Its Effect on the Immune System - S.L. Niankovskyi; V.V. Podolianska (Zaslavsky O.Yu., 2015)
Introduction. Recently, the issue of environmental pollution with various trace elements becomes increasingly important. Especially their adverse effects, even in small concentrations, on the health of children, in particular the immune system, because the child's body is more susceptible to their accumulation in the process of the development. Objective. To evaluate the load of micronutrients in children - the inhabitants of the modern city of Lviv (Western Ukraine) and correlation of immunity parameters with their imbalance. Materials and methods. Using selected randomized copy-pair method, in 50 pairs (n = 100) of healthy children aged 6-15 years who lived in the area of research and rural regions from the birth, we have analyzed the contents of some heavy metals (toxic Pb, Cd and conditionally essential Fe, Cu, Zn, Mn, Co, Cr, Ni) in the hair by atomic absorption spectrophotometry. Immune status of children has been assessed in terms of composition and expression of surface phenotypes of immune competent cells by direct immunofluorescence using monoclonal antibody panel. Mathematical processing of the findings was carried out by the methods of parametric and nonparametric statistics. Results. The content of heavy metals in children who live in modern cities is exceeded several times. At the same time, there was a reduction of conditionally essential micronutrients. The analysis of correlations between the main indicators of immunogram and concentration of trace elements in biological substrates of children found a close relationship between them, which confirmed the influence of environmental factors on the basic immunological parameters. Mathematical equations also confirmed the presence of factorial-effective relationship in the «environmental pollution - morbidity - micronutrient composition of biosubstrates - immune status» system and have a prognostic significance. Conclusion. Studies have shown that immune status, trace element composition of biological media of the organism and comprehensive assessment of the relationship make it possible to consider these figures as criteria of environmental risk.